The Dynamics of Shared Leadership in Institutional Management: The Case of Public Universities in Uganda - Sekiwu, Denis; Kaggwa, Victoria Tamale (Advances in Social Sciences Research Journal, 2017)
This study investigated the dynamics of shared leadership in university management in Uganda. Using data from two public universities and a sample of 100 participants, the results from a univariate analysis show that, the practice of shared leadership in university has since improved but much felt at the lower and middle-line management levels. Employing a Factor Analysis, a host of factors influencing shared leadership in a university management context have been reduced whereby institutional cohesion, expert contacts and shared responsibility are highly valued factors; mutual support, communicating institutional expectations, and autonomy and self-management are moderately valued factors; while networking for a common institutional vision is least valued as motivators of shared leadership in university management in Uganda. The researchers concluded that shared leadership can be optimally practiced where a participative management model prevails to allow room for the vertical distribution of authority throughout all the institutional structures.